O temor secreto dos perigos da alma: uma revisão bibliográfica sobre o conceito do medo na psicologia analítica - Morelli, Paula Nogueira de Toledo (2009)
The aim of this dissertation is to formulate a hypothesis regarding fear, as well as how conceive it in a clinical context, parting from a bibliographical review of the concept of fear in the collect works of C. G. Jung and other authors of Analytical Psychology. A qualitative method of research is used, through a bibliographical review of the CAPES and Scielo portal websites, articles and books on the approach. To illustrate the question of fear Chico Buarque de Holanda s tale Little Yellow Riding Hood is used. It is concluded that fear may be a protective and disturbing emotion of the ego, as well as a signal of the changes in the stages of development. The study finishes pointing out the meanings of fear in the Jungian clinic, as well was the ways of dealing with it